The use of innovative technologies in the teaching of fine arts in the system of continuing education - Ergashev Madaminjon Yuldashevich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
In this article, the subject of fine arts, interest in the use of pedagogical and information technologies, interactive methods and innovative lessons in the educational process, non-traditional teaching methods, stratification, group work, conversation, discussion, database, "Brainstorming" , Methods such as “Cluster- Network”, “Sunflower”, “Boomerang”, “Museum”, “Presentation-Presentation” are based on the essence of their content - to attract the child's attention, not to be bored, to work together, to encourage lessons, to share their opinions comparison, the introduction of a sincere debate, the fact that it gives good results according to the principles of encouraging active participation